METODE MEHAR UNTUK SOLUSI OPTIMAL FUZZY DAN ANALISA SENSITIVITAS PROGRAM LINIER DENGAN VARIABEL FUZZY BILANGAN TRIANGULAR - Marlia Ulfa Marlia Ulfa (MATEMATIKA FSM, UNDIP, 2016)
ABSTRACT. Fuzzy linear programming problems containing closely with uncertainty about the parameters. Changes in the value of the parameters without changing the optimal solution or change the optimal solution is called sensitivity analysis. Sensitivity analysis is a basic for studying the effect of the changes that occur to the optimal solution. Linear programming with fuzzy variable is a form of fuzzy linear program is not fully because there are objective function coefficients and coefficients of constraints that are crisp numbers. Resolving the problem of linear programming with fuzzy variables by using mehar method will get solutions and optimal fuzzy value and solutions and optimal crisp value. To solve the problem of linear program with fuzzy variable is using mehar, must be converted beforehand in the form of crisp linear programming. This thesis explores mehar method to solve linear programming problems with fuzzy variables with triangular number and a sensitivity analysis on the optimum solution FVLP so that when there is a change of data of the problem, new solution will remain optimal.